The Role of Experiential Learning in Developing Aesthetic and Creative Skills in Art Education - Raxmonova E’zoza Zoir qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines the role of experiential learning in enhancing students’ aesthetic perception and creative skills in art education. It explores methods such as hands-on workshops, field trips, collaborative projects, and interactive exercises to engage learners actively in the artistic process. The study emphasizes the importance of providing an immersive and supportive environment that nurtures originality, critical thinking, and cultural appreciation.